Phase-Shifted Full-Bridge Zero Voltage Switching DC-DC Converter Design with MATLAB/Simulink Implementation - Oladimeji Ibrahim; Nor Zaihar Yahaya; Nordin Saad (International Journal of Electrical and Computer Engineering (IJECE), 2018)
Design of phase-shifted full bridge zero voltage switching DC-DC converter has been very challenging due to circuit parasitic effect on the system dynamics. This paper presents steady-state analysis and iterative approach for the systemic design of phase-shifted full bridge DC-DC converter with improved dynamic performance and satisfactory operational requirement in terms of zero-voltage switching range, operating switching frequency and switching resonance. A 3 kW DC-DC converter is designed using the iterative design approach and the system dynamics performance was investigated in the MATLAB/Simulink environment. The converter zero-voltage switching simulation results were satisfactory with 90% efficiency under full load condition.